1. Please could you give me a hand with deriving the following equation: x1m=(x1CMC2)/(x1CMC2+x2CMC1) 2. Relevant equations Eq 1: 1/CMC=x1/CMC1+x2/CMC2 Eq 2: CMC=x1mCMC1+x2mCMC2 Eq 3: x1+x2=1 3. The attempt at a solution 1. invert Eq 2 and equate with Eq 1. 2. eliminate x2m using the fact that x2m=(1-x1m) 3. Rearrange.. I get to the following and don't know how to get closer to the solution. I've got a feeling I'm missing something obvious. x1m=[(CMC1/x1)+(CMC2/x2)-CMC2)]/(CMC1-CMC2) Please help! Thank you in advance.